Identification and characterization of thermotolerant acetic acid bacteria strains isolated from coconut water vinegar in Sri Lanka. Issue 3 (4th March 2014) - Perumpuli, PABN; Watanabe, Taisuke; Toyama, Hirohide
Abstract: From the pellicle formed on top of brewing coconut water vinegar in Sri Lanka, three Acetobacter strains (SL13E-2, SL13E-3, and SL13E-4) that grow at 42 °C and four Gluconobacter strains (SL13-5, SL13-6, SL13-7, and SL13-8) grow at 37 °C were identified as Acetobacter pasteurianus and Gluconobacter frateurii, respectively. Acetic acid production by the isolated Acetobacter strains was examined. All three strains gave 4% acetic acid from 6% initial ethanol at 37 °C, and 2.5% acetic acid from 4% initial ethanol at 40 °C. Compared with the two other strains, SL13E-4 showed both slower growth and slower acetic acid production. As well as the thermotolerant SKU1108 strain, the activities of the alcohol dehydrogenase and the aldehyde dehydrogenase of SL13E-2 and SL13E-4 were more stable than those of the mesophilic strain. The isolated strains were used to produce coconut water vinegar at higher temperatures than typically used for vinegar production. Graphical abstract: : From the pellicle formed on top of brewing coconut water vinegar in Sri Lanka, three Acetobacter pasteurianus strains and four Gluconobacter frateurii strains were isolated.